«El mundo al revés»: resistencia y adaptación cultural entre los indios de la ciudad de Lima de inicios del siglo XVII - Vega Loyola, José Javier (2025)
The manifestations of resistance and cultural adaptation among the indigenous immigrant population in the city of Lima at the beginning of the 17th century are analyzed. For this purpose, historical and documentary information was reviewed, mainly the records of the Lima Indian Registry from 1613. It was found that among the Indian immigrants there were manifestations of cultural resistance at the level of identity, work activity, social organization, consumption habits, and the continuity of some cultural traditions. But there were also manifestations of adaptation of Christian-Hispanic names, practice of Spanish artisan trades, participation in Catholic traditions, ladinization, formation of artisan guilds and Indian brotherhoods. It was concluded that resistance as well as cultural adaptation developed in a complementary way, thus learning the Spanish language, the economic activity carried out and Christianization not only allowed them to integrate into society, but also to respond from a better position.